Mark E. Nissen: Harnessing Knowledge Dynamics: Principled Organizational Knowing & Learning - Carroll,Tim (2008)
Harnessing Knowledge Dynamics: Principled Organizational Knowing & Learning by Mark E. Nissen is reviewed.
Keywords: Management